2018
DOI: 10.1152/japplphysiol.01110.2017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of contractile activity on PGC-1α transcription in young and aged skeletal muscle

Abstract: Mitochondrial impairments are often noted in aged skeletal muscle. The transcriptional coactivator peroxisome proliferator-activated receptor-γ coactivator-1α (PGC-1α) is integral to maintaining mitochondria, and its expression declines in aged muscle. It remains unknown whether this is due to a transcriptional deficit during aging. Our study examined PGC-1α transcription in muscle from young and old F344BN rats. Using a rat PGC-1α promoter-reporter construct, we found that PGC-1α transcription was reduced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 57 publications
0
30
0
Order By: Relevance
“…Although this remains controversial, recent work has indicated that aged muscle can increase the transcription of PGC‐1α in response to contractile activity (Carter et al . ), as well as enhance its translational capacity in response to a training regime (Robinson et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although this remains controversial, recent work has indicated that aged muscle can increase the transcription of PGC‐1α in response to contractile activity (Carter et al . ), as well as enhance its translational capacity in response to a training regime (Robinson et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, following exercise training protocols, aged muscle appears to harbour a lower capacity for the generation of new, healthy organelles than younger counterparts (Hood et al 2016). Although this remains controversial, recent work has indicated that aged muscle can increase the transcription of PGC-1α in response to contractile activity (Carter et al 2018), as well as enhance its translational capacity in response to a training regime (Robinson et al 2017). Nonetheless, little research has focused on the selective removal of organelles through mitophagy, a process also critical to maintaining organelle and muscle integrity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mitochondrial redox signaling activates guanosine triphosphatase (GTPase) RhoA, which subsequently triggers accumulation of F-actin, beneficial for the repair of local injury. A self-standing field beyond the scope of this article represents studies of aged skeletal muscle and relations to a sedentary life-style [32]. We should at least note that overexpression of PGC1α in aging muscle led to a reversal of the observed age-related changes [33].…”
Section: Exercise Evoked Mitochondrial Signaling Targets Pgc1α In Skementioning
confidence: 96%